Factors influencing consumer perception towards Electronic Payment (E-Payment) in Melaka / Ahmad Tarmizi Abu Zaki - Abu Zaki, Ahmad Tarmizi (Faculty of Business and Management, 2019)
This study examines the factors influencing consumers’ perception towards electronic payment (e-payment) in Melaka. Consumers’ perception of electronic payment is a broad scope that encompasses many determinants but the researcher specifically focuses on five determinants namely benefits, trust, self-efficacy, ease of use and security. Data were collected from 181 respondents using convenience sampling. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 25 Software. Using SPSS, numerous tests were converged such as reliability analysis, descriptive analysis, Pearson’s correlation analysis and multiple regression analysis. The result indicated that there are a positive significant relationship between benefits and ease of use towards consumers’ perception of e-payment. However, trust, self-efficacy, and security recorded as insignificant relationship towards consumers’ perception of e-payment. Recommendation and direction for future studies were discussed at the end of the study.